THE ROMANCE FORMULA IN CECELIA AHERN’S LOVE, ROSIE - Santoso, Distania; Basuki, Imam; Wardani, L. Dyah Purwita (Lentera: Jurnal Ilmiah Kependidikan, 2019)
This research analyzes the romance formula presented in Love, Rosie by discussing the standard convention of the novel. The romance formula analysis tends to prove what is the sociocultural background in 20th century of Ireland society which becomes the cultural background of the novel. We discuss the issues among popular culture and also finding out the dominant components of the story which builds the story into a romance story. The discussion is employed the Cawelti’s concept and supported by Radway’s theory of romance. This study discusses Romance formula in Love Rosie is presented by the two dominant elements, those are the romance plot formula and the characters. The inventions of the romance formula in Love Rosie is found in the writing style of the novel. The novel is written in the form of instant messages and letters that are sent between the hero and heroine. The results of this study indicate that Love, Rosie has two dominant elements that built the story into a romance story. The first element is the story plot and the second is the main characters of the story whom develops the love relationship in the story, which are the hero and the heroine. The story plot of Love, Rosie can be classified into four stages, those are the first meeting of Alex and Rosie, Alex and Rosie fall in love to each other, Obstacles which contain the internal and external conflicts of the hero and heroine, and the ending of the story.